Semiotic Analysis of Memes Insulting Others on Facebook - Putriayunda, Putriayunda; Aditiawarman, Mac (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This research is entitled semiotic analysis of memes insulting others on Facebook. The semiotic study aims to explain the signs as well as to know the meanings of dark joke memes on Facebook social media. The theory used in this study is Peirce's theory, namely by using the triadic model. The method used in this study is by using a qualitative descriptive method. The data analysis method uses the second data, namely the uploaded image and the researcher selects it by taking a screenshot and then interpreting. Data collection techniques used are observation, documentation and note-taking techniques. Peirce's semiotic analysis is an analytical technique that researchers use to find out the signs and meanings of dark joke meme images on Facebook social media, namely the triadic model consisting of representamen, object and interpretant. The results of this study, namely being able to find out the signs and meanings that exist in writing and images of dark joke memes on Facebook social media.